2022
DOI: 10.3389/fsufs.2021.691786
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Groundnut Residues to Soil N and the Influence of Farmer Management in Western Uganda

Abstract: Through symbiotic biological nitrogen fixation (BNF), grain legumes, such as groundnuts, can enhance soil nitrogen (N) and be an important source of N fertility, as well as a critical component of human nutrition and food security. Because legumes obtain N from soil N stocks as well as BNF, legume residues are key to capturing potential N benefits for soils, which may contribute to increased yields and food production. Here, we conducted a detailed survey at household and field level within a six-village corri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The combined use of chemical fertilizers and organic manure may have increased organic matter and further mineralization, resulting in an increase in available N, P, and K status. In addition, legumes such as groundnuts, can improve soil nitrogen (N) and be an important contributor of N fertility through symbiotic biological nitrogen fixation (Witcombe and Tiemann, 2022). Significance of combination of different availability indices of N, P and K Various combinations of different availability indices of N, P and K are given in table 2 for groundnut and in table 3 for wheat.…”
Section: Resultsmentioning
confidence: 99%
“…The combined use of chemical fertilizers and organic manure may have increased organic matter and further mineralization, resulting in an increase in available N, P, and K status. In addition, legumes such as groundnuts, can improve soil nitrogen (N) and be an important contributor of N fertility through symbiotic biological nitrogen fixation (Witcombe and Tiemann, 2022). Significance of combination of different availability indices of N, P and K Various combinations of different availability indices of N, P and K are given in table 2 for groundnut and in table 3 for wheat.…”
Section: Resultsmentioning
confidence: 99%
“…This may have contributed to an increase in the total nitrogen in the soil after the decomposition of the groundnut residues thus enhancing the vegetative growth of the cassava plants in the intercropping system to some extent. residues have the potential to contribute to total nitrogen stocks if retained in the field [10]. Even though intercropping had no significant influence on the aboveground biomass of cassava, the aboveground biomass for the sole cassava was higher than the intercropped cassava.…”
Section: Cassavamentioning
confidence: 92%
“…Average across locations, the SOC stock for the cassava-groundnut intercrop at harvest of the cassava increased by 3.4% when compared to the baseline. Previous research studies have shown that groundnut residues have the potential of increasing SOC if retained in the field, conversely, subsequent removal of the groundnut residues could lead to a sizable loss of SOC from the field [10].…”
Section: Changes In Soil Organic Carbon Stockmentioning
confidence: 98%
See 2 more Smart Citations